Framing dakwah salafi Rodja TV di media sosial youtube - Lukman Al- Hakim (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2021)
This study aims to analyze Rodja TV's Salafi Da'wah on Youtube social media using Robert M. Entman's framing model analysis. This study uses qualitative methods with field research and library data. The results of this study consist of four parts, namely: Define problems, Issues raised by Rodja TV about the manhaj of the salaf to straighten out the understanding of the salafi which has been considered incompatible with the Qur'an and Sunah. Diagnose causes, Causes The problem is because of the negative stigma that has already developed in society that salafi is a